Six-membered saturated NHC-stabilized borenium cations: isolation of a cationic analogue of borinic acid - Kundu, Gargi; Balayan, Kajal; Tothadi, Srinu; Sen, Sakya S. (Inorganic Chemistry, 2022)
The reaction of six-membered saturated NHC [1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene; henceforth abbreviated as 6-SIDipp] with PhBCl2 yields a Lewis base adduct, 6-SIDipp.PhBCl2 (1), which readily undergoes nucleophilic substitution reaction with AgNO3, leading to the single (2) and double (3) substitution of both chlorides with ONO2 moieties at the boron atom. The reaction of 1 with 1 equiv of AlCl3 resulted in a borenium cation of composition [6-SIDipp.B(Ph)Cl]+ (4) with AlCl4- as the counteranion. Although borenium cations with different substituents on boron have been reported, a structurally characterized phenylchloroborenium cation remains unknown. Similarly, the reaction of 1 with triflic acid provides the first representative of a new class of borenium cations bearing one hydroxyl and one phenyl group on boron (5), a cationic analogue of borinic acid. Ph-BN H Diphenylborinic acid

Synthesis of diamido N-heterocyclic imines (DAC = NH) via staudinger or reductive N-N bond cleavage approach - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
This report communicates the first examples of N-heterocyclic imines based on electrophilic diamido carbenes (DACs). While 2 is prepared by classical Staudinger synthesis, 4 is obtained via an unusual reductive N-N bond cleavage of an azine by HCl. The exocyclic C=N bond lengths in 2 and 4 are substantially shorter than those based on N-heterocyclic carbenes and cyclic (alkyl)(amino)carbene reflecting the electrophilic character of DACs.